Transformasi Teknologi Digital Dalam Pelayanan Pengadilan Dan Tantangan Implementasi E-Court Di Indonesia - NurLaeli SukestiArianiNasution ArianiNasution (Faculty of Law, Universitas Wijayakusuma, 2021)
This article intends to explain the transformation of Indonesian courts and judiciary from conventional to digital (e-court) models. The implementation of an e-court is actually more than just a case administrative service, but also the implementation of electronic trial examinations, among which evidence is transformed into electronic documents. As a new practice in the Indonesian court environment, the main problem is the impact of digital technology transformation in court services, and efforts to face challenges in e-court implementation. This article uses a doctrinal method, so it relies on primary and secondary legal materials. The results of the analysis show that the electronic transformation creates efficiency based on the notion of the teachings of